Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1074/jbc.m111.281840
|View full text |Cite
|
Sign up to set email alerts
|

RNA-binding Site of Escherichia coli Peptidyl-tRNA Hydrolase

Abstract: Background: Bacterial peptidyl-tRNA hydrolase is essential in recycling of ribosome-dissociated peptidyl-tRNAs. Results: Comparing minimalist substrates and using NMR mapping, the RNA-binding site of the hydrolase is characterized. Conclusion: Interaction between the hydrolase and tRNA involves features common to all elongator tRNAs. Significance: Knowledge of a bacterial peptidyl-tRNA hydrolase⅐substrate complex may drive the search for enzyme inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…The structural difference within the acceptor stem part probably arose from the deletion of the D arm, anticodon arm and variable loop. However, a previous report demonstrated that the catalytic efficiency of Pth for the N -acetyl-histidyl-CCA-acceptor-TΨC domain of tRNA His is comparable to that for the N -acetyl-histidyl-full-length tRNA His (41), indicating that the deletion does not affect the interaction with Pth.
Figure 2.Overall structure of Pth in complex with the CCA-acceptor-TΨC domain of tRNA.
…”
Section: Resultsmentioning
confidence: 88%
“…The structural difference within the acceptor stem part probably arose from the deletion of the D arm, anticodon arm and variable loop. However, a previous report demonstrated that the catalytic efficiency of Pth for the N -acetyl-histidyl-CCA-acceptor-TΨC domain of tRNA His is comparable to that for the N -acetyl-histidyl-full-length tRNA His (41), indicating that the deletion does not affect the interaction with Pth.
Figure 2.Overall structure of Pth in complex with the CCA-acceptor-TΨC domain of tRNA.
…”
Section: Resultsmentioning
confidence: 88%
“…X-ray characterization of Pth with bound bases, substrate mimics, and acceptor-TψC fragments of tRNA have also been reported (Ito et al 2012;Kaushik et al 2013;Singh et al 2014a,b). NMR-based chemical shift perturbation studies have been carried out for EcPth in the presence of a minimal substrate analog (Giorgi et al 2011b), and uncharged fragments of tRNA (Giorgi et al 2011a). In the case of Pth enzymes, the catalytic site resides in a crevice on the surface of the protein.…”
Section: Introductionmentioning
confidence: 99%
“…Previous structural and mutagenesis studies showed that helix α6 directly interacts with the TΨC arm of the tRNA moiety of the substrate, and this interaction is necessary for the Pth activity. 60,61 Based on these facts, we infer that Pth is able to interact with the wide variety of tRNA species of its substrates by adjusting the position of helix α6.…”
Section: Flexibility and Dynamicsmentioning
confidence: 86%